IZUZECI OD NEPOSREDNOG IZVOĐENJA DOKAZA I PRIVILEGOVANI SVJEDOCI U KRIVIČNOM POSTUPKU CRNE GORE - Mirko Bošković (Revija za kriminologiju i krivično pravo)
This paper analyses practical issues when applying legal provisions dealing with the exemptions from direct presentation of evidence in the context of provisions on persons released from the duty to testify in criminal proceedings in Montenegro. After the amendments to the Criminal Procedure Code from 2015, the possibility of using the testimony of privileged witnesses from the investigation was introduced into the legislation, in situations when they exercise their right and refuse to testify at the main hearing. There will be explanation of standards of the European Court of Human Rights, the characteristics of the normative framework for exceptions to the principle of immediacy in the CPC of Montenegro, and the way in which our case law treats these issues. Finally, appropriate conclusions were drawn regarding the obvious conflict of norms, which arose after the mentioned legal amendments, and the potential violation of the rights of defendants to a fair trial due to their (inadequate) application.